Pengaruh Bonus Plan dan Firm Size terhadap Earning Management (Studi Empiris pada Perusahaan Manufaktur di BEI) - Naomi Nababan; Lisnawati Lisnawati (Institut Manajemen Wiyata Indonesia, 2018)
This study aims to analyze the effect of bonus plan, and firm size on earnings management. Earnings management is measured using discretionary accruals. The independent variables used in this study are the bonus plan of the board of directors and commissioners, and the size of the company while the dependent variable is earnings management. Several previous studies have shown mixed results. To get valid results, testing is carried out on each variable based on the hypothesis built. The study population is 143 manufacturing companies listed on the Indonesia Stock Exchange. The sample used was selected by purposive sampling method. After reduction with several criteria, 28 companies were identified as samples. The observation period is 2012-2016 years, so the number of samples used is 140 samples. Hypothesis testing is carried out using multiple linear regression analysis, determination coefficient, t test and f test. The results of this study indicate that company size affects earnings management, while bonus plans do not affect earnings management. This study has limitations, namely the bonus plan data used in this study is still in the form of total remuneration received by the board of directors and commissioners, where there are various components such as salaries, benefits, and bonuses. This study does not classify companies based on the size of the company owned by the company, and this research uses only two factors that can motivate earnings management in a company.